Inhibition of endoplasmic reticulum glucosidases is required for in vitro and in vivo dengue antiviral activity by the iminosugar UV-4 - Warfield, KL; Plummer, EM; Sayce, AC; Alonzi, DS; Tang, W; Tyrrell, BE; Hill, ML; Caputo, AT; Killingbeck, SS; Beatty, PR; Harris, E; Iwaki, R; et al. (Elsevier, 2016)
The antiviral activity of UV-4 was previously demonstrated against dengue virus serotype 2 (DENV2) in multiple mouse models. Herein, step-wise minimal effective dose and therapeutic window of efficacy studies of UV-4B (UV-4 hydrochloride salt) were conducted in an antibody-dependent enhancement (ADE) mouse model of severe DENV2 infection in AG129 mice lacking types I and II interferon receptors. Significant survival benefit was demonstrated with 10–20 mg/kg of UV-4B administered thrice daily (TID) for seven days with initiation of treatment up to 48 h after infection. UV-4B also reduced infectious virus production in in vitro antiviral activity assays against all four DENV serotypes, including clinical isolates. A set of purified enzyme, in vitro, and in vivo studies demonstrated that inhibition of endoplasmic reticulum (ER) α-glucosidases and not the glycosphingolipid pathway appears to be responsible for the antiviral activity of UV-4B against DENV. Along with a comprehensive safety package, these and previously published data provided support for an Investigational New Drug (IND) filing and Phases 1 and 2 clinical trials for UV-4B with an indication of acute dengue disease.